Restoring the Art of Healing: A Transcultural Psychiatry Case Report - Pordeus, Vitor (Journal of Psychology and Psychotherapy Research, 2014)
This paper reflects part of the 5 years experience in theatre and mental health developed by the Centre for Culture, Science and Health of the Office of Public Health, Rio de Janeiro. One selected Psychiatric Hospital Case is reported, and a short discussion about health and culture interplays under the proposed theoretical framework. It highlights historical experiences showing the importance of cultural and symbolic practices in mental and general health such as those studied by the Brazilian Psychiatrist Nise da Silveira and the contemporary paradigmatic shift of Biology and Health Sciences.